Derivation of Two Parameters Poisson Rani Distribution and Its Properties - Alao, Bamigbala Olateju; Peter, Pantuvo Tsoke; Babando, Ikrimat Aliyu; Gatta, Abdulganiy Abdullahi (Mikailalsys Journal of Mathematics and Statistics, 2025)
This study introduces the Two Parameters Poisson Rani Distribution (TPPRD). The probability distribution of TPPRD is derived by assuming that the parameters of the Poisson distribution follow the Two Parameters Rani Distribution, resulting in the formation of the TPPRD. The study derives some of its fundamental properties and demonstrates that TPPRD is a special-case distribution capable of handling overdispersed count data. Additionally, the maximum likelihood estimators are used to derive equations for estimating the parameters of the Two Parameters Poisson Rani Distribution.